The neurobiology of pain and facial movements in rodents: Clinical applications and current research - Domínguez-Oliva, Adriana; Mota-Rojas, Daniel; Hernández-Avalos, Ismael; Mora-Medina, Patricia; Olmos-Hernández, Adriana; Verduzco-Mendoza, Antonio; Casas-Alvarado, Alejandro; Whittaker, Alexandra L. (Frontiers in Veterinary Science, 2022)
One of the most controversial aspects of the use of animals in science is the production of pain. Pain is a central ethical concern. The activation of neural pathways involved in the pain response has physiological, endocrine, and behavioral consequences, that can affect both the health and welfare of the animals, as well as the validity of research. The strategy to prevent these consequences requires understanding of the nociception process, pain itself, and how assessment can be performed using validated, non-invasive methods. The study of facial expressions related to pain has undergone considerable study with the finding that certain movements of the facial muscles (called facial action units) are associated with the presence and intensity of pain. This review, focused on rodents, discusses the neurobiology of facial expressions, clinical applications, and current research designed to better understand pain and the nociceptive pathway as a strategy for implementing refinement in biomedical research.